An emerging public health threat: Mayaro virus increases its distribution in Peru - Aguilar-Luis M.A. (2020)
Background: The infection caused by Mayaro virus (MAYV), which presents as an acute febrile illness, is considered a neglected tropical disease. The virus is an endemic and emerging pathogen in South America and the Caribbean, responsible for occasional and poorly characterized outbreaks. Currently there is limited information about its expansion and risk areas. Methods: A cross-sectional study was performed in 10 urban primary care health centers in the Cajamarca region of Peru from January to June 2017. A total of 359 patients with suspected febrile illness were assessed. RNA was extracted from serum samples, following which MAYV real-time reverse transcriptase PCR (RT-PCR) for the detection of the nsP1 gene was performed. Results: MAYV was detected in 11.1% (40/359) of samples after RT-PCR amplification and confirmatory DNA sequencing. Most infections were detected in the adult population aged 18–39 years (40%) and 40–59 years (32.5%). Headache was the most frequent symptom in patients with MAYV infection (77.5%), followed by fever (72.5%), myalgia (55.0%), and arthralgia (50.0%). During the study, most of the MAYV cases were seen in May (47.5%) and April (35.0%), corresponding to the dry season (months without rain). Conclusions: This study is novel in describing the presence of MAYV in Cajamarca, an Andean region of Peru. Symptoms are non-specific and can be confused with those of other arbovirus or bacterial infections. Molecular biology methods such as RT-PCR allow the timely and accurate detection of MAYV and could thus be considered as a tool for surveillance in endemic areas. © 2020 The Author(s)